KONSEP PENDIDIKAN ISLAM IBNU KHALDUN DAN IMPLIKASINYA DI ERA 4.0 - Solehuddin, Moh; Abidin, Zainal (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
The purpose of this research is to examine the concept of Islamic education by Ibn Khaldun and its implications in the era of Industry 4.0. The research method used by the researcher is a literature review. The literature review is a research approach that gathers and analyzes information from various relevant literary sources. This method involves the process of searching, selecting, and critiquing existing literature to develop a comprehensive understanding of the researched subject. The findings of this research indicate that Ibn Khaldun's concept of education, as a 14th-century historian and philosopher, may not directly relate to the era of Industry 4.0, characterized by digital technology advancements and automation. However, some educational principles advocated by Ibn Khaldun can still hold relevance in the current educational context. The relevant aspects include holistic education, lifelong learning, and character education. However, the exemplary factor in education cannot be simply replaced by digitalization it is important to note that the educational context and demands today differ from Ibn Khaldun's time. Therefore, Ibn Khaldun's educational concepts need to be adapted and linked to the specific challenges and needs present in the era of Industry 4.0.